Juridical Analysis of Inheritance Law for Heirs Whose Presence Cannot Be Established According to the Civil Code - Alfian Kurniarizki; Arief Budiono; Turdialiev Mukhammad Ali Polatjon Ogli (Proceeding International Conference Restructuring and Transforming Law, 2023)
The heirs whose whereabouts cannot be known are heirs who have lost news so that it is not known whether he is still alive or dead. Or it can be called a missing person. In fact, many heirs ignore the inheritance rights of heirs whose whereabouts cannot be traced. Based on this background, this research was conducted with the aim of explaining the inheritance regulations for heirs whose whereabouts cannot be determined and the legal consequences for heirs whose existence is known after the distribution of inheritance. The research method used in this study is normative legal research using secondary data in the form of laws, court decisions, and related literature. This research also shows that in practice, there are various problems in determining the whereabouts of unknown heirs, such as difficulties in finding sufficient information and evidence to determine the existence of heirs, as well as differences of opinion regarding whether unknown heirs are entitled to receive a share of the inheritance.